Pengaruh Kompetensi Sumber Daya Manusia, Budaya Organisasi Dan Pengalaman Kerja Terhadap Kualitas Laporan Keuangan Di Bank Perkreditan Rakyat (Bpr) Se- Kecamatan Mengwi - Pradnyani, Ni Made Rina; Indraswarawati, Sang Ayu Putu Arie; Satriya, I Wayan Budi (UNHI Press, 2025)
The financial statements are prepared to provide relevant information regarding the financial position and all transactions carried out by the reporting entity during a reporting period. This study aims to analyze the effect of understanding human resources, organizational culture and work experience on the quality of financial reports in BPRs throughout the Mengwi District. The research was conducted at BPRs throughout the Mengwi District. The sampling method used purposive sampling and obtained 86 employees who prepared financial reports. Data analysis techniques using multiple linear regression, instrument test, classical assumption test, and model feasibility test. The results of the study show that human resource competence, organizational culture, and work experience have a positive and significant effect on the quality of financial reports in BPRs throughout the Mengwi district.